Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Recent Chemo-morphological coma evolution of comet 67P/Churyumov–Gerasimenko - Brian P. Murphy; Cyrielle Opitom; Colin Snodgrass; Sophie E. Deam; Léa Ferellec; Matthew Knight; Vincent Okoth; Bin Yang (Planetary and Space Science, 2025)

Correction: The IGCP 714 Project “3GEO– Geoclimbing & Geotrekking in Geoparks”– Selection of Geodiversity Sites Equipped for Climbing for Combining Outdoor and Multimedia Activities - Irene Maria Bollati; Anna Masseroli; Mohammed Al Kindi; Lucas Cezar; Anna Chrobak-Žuffová; Ashish Dongre; Charalampos Fassoulas; Eugenio Fazio; Manuel Garcia-Rodríguez; Jasper Knight; Jack J. Matthews; Ricardo Galeno Fraga de Araújo Pereira; et al. (Geoheritage, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Individual identification in acoustic recordings - Elly Knight; Tessa Rhinehart; Devin R. de Zwaan; Matthew J. Weldy; Mark Cartwright; Scott H. Hawley; Jeffery L. Larkin; Damon Lesmeister; Erin Bayne; Justin Kitzes (Trends in Ecology & Evolution, 2024)

The IGCP 714 Project “3GEO – Geoclimbing & Geotrekking in Geoparks” – Selection of Geodiversity Sites Equipped for Climbing for Combining Outdoor and Multimedia Activities - Irene Maria Bollati; Anna Masseroli; Mohammed Al Kindi; Lucas Cezar; Anna Chrobak-Žuffová; Ashish Dongre; Charalampos Fassoulas; Eugenio Fazio; Manuel Garcia-Rodríguez; Jasper Knight; Jack J. Matthews; Ricardo Galeno Fraga de Araújo Pereira; et al. (Geoheritage, 2024)
The IGCP 714 project “3GEO – Geoclimbing & Geotrekking in Geoparks ” is financed by the International Geoscience Programme (IGCP) and supported by the International Union of Geological Sciences (IUGS). In this paper, we report on the results of the first phase of the project focused on the criteria to be adopted to select geodiversity sites equipped for climbing or trekking. The selection of geoclimbing sites and geotrekking routes is aimed at combining multimedia tools and outdoor activities for Geosciences promotion and conservation in UNESCO Global Geoparks, aspiring geoparks or geoparks project, and also in protected areas featuring geoheritage sites. Indeed, both outdoor activities and multimedia tools favour the pursuing of many of the United Nations Sustainable Development Goals (e.g., 3, 4, 8, 11). An international consortium of geoscientists from 12 different countries selected, through the proposed procedure, 22 geoclimbing sites, and then they also detected 30 geotrekking routes mirroring Earth geodiversity. At some test sites (geoclimbing and geotrekking) multimedia tools and digital outcrop models have been developed through different methodological approaches (e.g., Structure from Motion and Multi-View Stereo photogrammetry), to open the way to the second part of the project still in progress. These sites and the relative virtual models are herein also shown. The final aim of the IGCP 714 project is indeed to create an open data repository (digital outcrop models, videos, virtual tours, photos, scientific information, and interpretations) to upload data of the selected sites to mirror Earth geodiversity for different users including tourists and school groups.

To what extent can decommissioning options for marine artificial structures move us toward environmental targets? - Antony M. Knights; Anaëlle J. Lemasson; Louise B. Firth; Nicola Beaumont; Silvana Birchenough; Jeremy Claisse; Joop W.P. Coolen; Andrea Copping; Michela De Dominicis; Steven Degraer; Michael Elliott; Paul G. Fernandes; et al. (Journal of Environmental Management, 2024)

Soil and bark biodiversity forms discrete islands between vineyards that are not affected by distance or management regime - Lucie Jiraska; Beatrix Jones; Sarah J. Knight; Jed Lennox; Matthew R. Goddard (Environmental Microbiology, 2023)
Within geographic regions, the existing data suggest that physical habitat (bark, soil, etc.) is the strongest factor determining agroecosystem microbial community assemblage, followed by geographic location (site), and then management regime (organic, conventional, etc.). The data also suggest community similarities decay with increasing geographic distance. However, integrated hypotheses for these observations have not been developed. We formalized and tested such hypotheses by sequencing 3.8 million bacterial 16S, fungal ITS2 and non‐fungal eukaryotic COI barcodes deriving from 108 samples across two habitats (soil and bark) from six vineyards sites under conventional or conservation management. We found both habitat and site significantly affected community assemblage, with habitat the stronger for bacteria only, but there was no effect of management. There was no evidence for community similarity distance–decay within sites within each habitat. While communities significantly differed between vineyard sites, there was no evidence for between site community similarity distance–decay apart from bark bacterial communities, and no correlations with soil and bark pH apart from soil bacterial communities. Thus, within habitats, vineyard sites represent discrete biodiversity islands, and while bacterial, fungal and non‐fungal eukaryotic biodiversity mostly differs between sites, the distance by which they are separated does not define how different they are.

Ecosystem resilience to invasion and drought: Insights after 24 years in a rare never‐grazed grassland - Michael C. Duniway; Rebecca Finger‐Higgens; Erika L. Geiger; David L. Hoover; Alix A. Pfennigwerth; Anna C. Knight; Matthew Van Scoyoc; Mark Miller; Jayne Belnap (Global Change Biology, 2023)
Understanding the resilience of ecosystems globally is hampered by the complex and interacting drivers of change characteristic of the Anthropocene. This is true for drylands of the western US, where widespread alteration of disturbance regimes and spread of invasive non‐native species occurred with westward expansion during the 1800s, including the introduction of domestic livestock and spread of Bromus tectorum , an invasive non‐native annual grass. In addition, this region has experienced a multi‐decadal drought not seen for at least 1200 years with potentially large and interacting impacts on native plant communities. Here, we present 24 years of twice‐annual plant cover monitoring (1997–2021) from a semiarid grassland never grazed by domestic livestock but subject to a patchy invasion of B. tectorum beginning in ~1994, compare our findings to surveys done in 1967, and examine potential climate drivers of plant community changes. We found a significant warming trend in the study area, with more than 75% of study year temperatures being warmer than average (1966–2021). We observed a native perennial grass community with high resilience to climate forcings with cover values like those in 1967. In invaded patches, B. tectorum cover was greatest in the early years of this study (1997–2001; ~20%–40%) but was subsequently constrained by climate and subtle variation in soils, with limited evidence of long‐term impacts to native vegetation, contradicting earlier studies. Our ability to predict year‐to‐year variation in functional group and species cover with climate metrics varied, with a 12‐month integrated index and fall and winter patterns appearing most important. However, declines to near zero live cover in recent years in response to regional drought intensification leave questions regarding the resiliency of intact grasslands to ongoing aridification and whether the vegetation observations reported here may be a leading indicator of impending change in this protected ecosystem.

Life-Cycle and Applicational Analysis of Hydrogen Production and Powered Inland Marine Vessels - Matthew Knight; Eduardo Blanco-Davis; Oliver Platt; Milad Armin (Journal of Marine Science and Engineering, 2023)
Green energy is at the forefront of current policy, research, and engineering, but some of the potential fuels require either a lot of deeper research, or a lot of infrastructure before they can be implemented. In the case of hydrogen both are true. This report aims to analyse the potential of hydrogen as a future fuel source by performing a life-cycle assessment. Through this the well-to-tank phase of fuel production, and the usage phase of the system have been analysed. Models have also been created for traditional fuel systems to best compare results. The results show that hydrogen has great potential to convert marine transport to operating off green fuels when powered through low-carbon energy sources, which could reduce a huge percentage of the international community’s greenhouse gas emissions. Hydrogen produced through wind powered alkaline electrolysis produced emission data 5.25 g of CO2 equivalent per MJ, compared to the 210 g per MJ produced by a medium efficiency diesel equivalent system, a result 40 times larger. However, with current infrastructure in most countries not utilising a great amount of green energy production, the effects of hydrogen usage could be more dangerous than current fuel sources, owing to the incredible energy requirements of hydrogen production, with even grid (UK) powered electrolysis producing an emission level of 284 g per MJ, which is an increase against standard diesel systems. From this the research concludes that without global infrastructure change, hydrogen will remain as a potential fuel rather than a common one.

Field evaluation of electrostatic precipitators for particulate matter mitigation in a manure-belt layer facility - Reyna M. Knight; Matthew J. Herkins; Jeb S. Hocter; Shannon R. Milliken; Lingying Zhao; Heping Zhu (Biosystems Engineering, 2023)

Development and optimisation of full-scale prototype electrostatic precipitators in a laboratory for particulate matter mitigation in poultryfacilities - Reyna M. Knight; Jeb S. Hocter; Shannon R. Milliken; Matthew J. Herkins; Lingying Zhao; Heping Zhu (Biosystems Engineering, 2023)

The effect of shade on sheep grazing pasture during summer conditions - Matthew I. Knight; Nick P. Linden; Kym L. Butler; Maxine Rice; Eric N. Ponnampalam; Ralph Behrendt; Ellen C. Jongman (Journal of Veterinary Behavior, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Ocean Acidification Mitigates the Negative Effects of Increased Sea Temperatures on the Biomineralization and Crystalline Ultrastructure of Mytilus - Antony M. Knights; Matthew J. Norton; Anaëlle J. Lemasson; Natasha Stephen (Frontiers in Marine Science, 2020)

Loss of vacuolar acidity results in iron-sulfur cluster defects and divergent homeostatic responses during aging in Saccharomyces cerevisiae - Kenneth L. Chen; Toby N. Ven; Matthew M. Crane; Matthew L. C. Brunner; Adrian K. Pun; Kathleen L. Helget; Katherine Brower; Dexter E. Chen; Ha Doan; Justin D. Dillard-Telm; Ellen Huynh; Yen-Chi Feng; et al. (GeroScience, 2020)

Effects in rats of adolescent exposure to cannabis smoke or THC on emotional behavior and cognitive function in adulthood - Adriaan W. Bruijnzeel; Parker Knight; Stefany Panunzio; Song Xue; Matthew M. Bruner; Shannon C. Wall; Marjory Pompilus; Marcelo Febo; Barry Setlow (Psychopharmacology, 2019)

Development of a quantitative PCR method for screening ichthyoplankton samples for bigheaded carps - Andrea K. Fritts; Brent C. Knights; James H. Larson; Jon J. Amberg; Christopher M. Merkes; Tariq Tajjioui; Steven E. Butler; Matthew J. Diana; David H. Wahl; Michael J. Weber; John D. Waters (Biological Invasions, 2019)

Mapping of new quantitative trait loci for sudden death syndrome and soybean cyst nematode resistance in two soybean populations - Sivakumar Swaminathan; Nilwala S. Abeysekara; Joshua M. Knight; Min Liu; Jia Dong; Matthew E. Hudson; Madan K. Bhattacharyya; Silvia R. Cianzio (Theoretical and Applied Genetics, 2018)

Habitat size modulates the influence of heterogeneity on species richness patterns in a model zooplankton community - Matthew S. Schuler; Jonathan M. Chase; Tiffany M. Knight (Ecology, 2017)
Habitat heterogeneity is a primary mechanism influencing species richness. Despite the general expectation that increased heterogeneity should increase species richness, there is considerable variation in the observed relationship, including many studies that show negative effects of heterogeneity on species richness. One mechanism that can create such disparate results is the predicted trade‐off between habitat area and heterogeneity, sometimes called the area‐heterogeneity‐trade‐off ( AHTO ) hypothesis. The AHTO hypothesis predicts positive effects of heterogeneity on species richness in large habitats, but negative effects in small habitats. We examined the interplay between habitat size and habitat heterogeneity in experimental mesocosms that mimic freshwater ponds, and measured responses in a species‐rich zooplankton community. We used the AHTO hypothesis and related mechanisms to make predictions about how heterogeneity would affect species richness and diversity in large compared to small habitats. We found that heterogeneity had a positive influence on species richness in large, but not small habitats, and that this likely resulted because habitat specialists were able to persist only when habitat size was sufficiently large, consistent with the predictions of the AHTO hypothesis. Our results emphasize the importance of considering context (e.g., habitat size in this case) when investigating the relative importance of ecological drivers of diversity, like heterogeneity.

Potential Species Replacements for Black Ash (Fraxinus nigra) at the Confluence of Two Threats: Emerald Ash Borer and a Changing Climate - Louis Iverson; Kathleen S. Knight; Anantha Prasad; Daniel A. Herms; Stephen Matthews; Matthew Peters; Annemarie Smith; Diane M. Hartzler; Robert Long; John Almendinger (Ecosystems, 2016)

Mapping the ‘breaker’ element of the gametocidal locus proximal to a block of sub-telomeric heterochromatin on the long arm of chromosome 4Ssh of Aegilops sharonensis - Emilie Knight; Ashleigh Binnie; Tracie Draeger; Matthew Moscou; María-Dolores Rey; Justine Sucher; Surbhi Mehra; Ian King; Graham Moore (Theoretical and Applied Genetics, 2015)

Antifungal isolates database of amphibian skin‐associated bacteria and function against emerging fungal pathogens - Douglas C. Woodhams; Ross A. Alford; Rachael E. Antwis; Holly Archer; Matthew H. Becker; Lisa K. Belden; Sara C. Bell; Molly Bletz; Joshua H. Daskin; Leyla R. Davis; Sandra V. Flechas; Antje Lauer; et al. (Ecology, 2015)
Microbial symbionts of vertebrate skin have an important function in defense of the host against pathogens. In particular, the emerging chytrid fungus Batrachochytrium dendrobatidis , causes widespread disease in amphibians but can be inhibited via secondary metabolites produced by many different skin‐associated bacteria. Similarly, the fungal pathogens of terrestrial salamander eggs Mariannaea elegans and Rhizomucor variabilis are also inhibited by a variety of skin‐associated bacteria. Indeed, probiotic therapy against fungal diseases is a recent approach in conservation medicine with growing experimental support. We present a comprehensive Antifungal Isolates Database of amphibian skin‐associated bacteria that have been cultured, isolated, and tested for antifungal properties. At the start, this database includes nearly 2000 cultured bacterial isolates from 37 amphibian host species across 18 studies on five continents: Africa, Oceania, Europe, and North and South America. As the research community gathers information on additional isolates, the database will be updated periodically. The resulting database can serve as a conservation tool for amphibians and other organisms, and provides empirical data for comparative and bioinformatic studies. The database consists of a FASTA file containing 16S rRNA gene sequences of the bacterial isolates, and a metadata file containing information on the host species, life‐stage, geographic region, and antifungal capacity and taxonomic identity of the isolate.

Influence of priority effects and pond location on invaded larval amphibian communities - C. Michael Knight; Matthew J. Parris; William H. N. Gutzke (Biological Invasions, 2009)

Volcanic stratigraphy of large-volume silicic pyroclastic eruptions during Oligocene Afro-Arabian flood volcanism in Yemen - Ingrid Ukstins Peate; Joel A. Baker; Mohamed Al-Kadasi; Abdulkarim Al-Subbary; Kim B. Knight; Peter Riisager; Matthew F. Thirlwall; David W. Peate; Paul R. Renne; Martin A. Menzies (Bulletin of Volcanology, 2005)

Genetic prion disease: the EUROCJD experience - Gábor G. Kovács; Maria Puopolo; Anna Ladogana; Maurizio Pocchiari; Herbert Budka; Cornelia van Duijn; Steven J. Collins; Alison Boyd; Antonio Giulivi; Mike Coulthart; Nicole Delasnerie-Laupretre; Jean Philippe Brandel; et al. (Human Genetics, 2005)

Construction and integration of radiation-hybrid and cytogenetic maps of dog Chromosome X - Helen F. Spriggs; Nigel G. Holmes; Matthew Breen; Panos Deloukas; Cordelia F. Langford; Mark T. Ross; Nigel P. Carter; Maria E. Davis; Catherine Knights; Angela Smith; Christine J. Farr; Linda C. McCarthy; et al. (Mammalian Genome, 2003)

Decrease of phosphoribulokinase activity by antisense RNA in transgenic tobacco: definition of the light environment under which phosphoribulokinase is not in large excess - Matthew J. Paul; Simon P. Driscoll; P. John Andralojc; Jacqui S. Knight; John C. Gray; David W. Lawlor (Planta, 2000)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)